Я такая прекрасная ужасная! - Мист Магнус (Маленькая злая книга, 2022)
Экземпляры: ф.6 (20230424) / Инвентарный номер: 3960 И / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: М 65 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-44